Some aspects of prevention of postoperative relapse in patients with nodular forms of goiter - N.P. Tkachuk; V.V. Bilookyi; Ya.V. Gyrla (Mìžnarodnij Endokrinologìčnij Žurnal, 2017)
Background. Annual prevalence of nodular forms of goiter leads to an increase in the number of surgeries, and therefore, to an increase of postoperative complications. According to different authors, from 3 to 80 % of patients suffering from nodular forms of goiter are operated in case of relapse. This wide range can be caused by the lack of a unified monitoring system, prediction and prevention of relapses during postoperative period. The purpose of the study: to assess the prognostic possibilities of the developed scale to predict the risk of nodular goiter relapse. Materials and methods. 100 case histories of patients suffering from nodular forms of goiter was the material for retrospective study. The main group included 40 persons operated for the second time on goiter relapse; comparison group included 60 persons without relapse. Eighty patients with different forms of goiter became a clinical material for prospective study. The main group consisted of 40 patients with nodular goiter. To choose the volume of surgery in this group, the relapse risk prognostic scale concerning nodular form of goiter was used. The comparison group included 40 patients who underwent surgery without the use of the scale. Results. The retrospective analysis conducted has drawn our attention to the fact that in 80 % of patients with relapse of goiter, the first surgery was sparing, while in 90 % of them, radical surgical would be reasonable. Hemi- or thyroidectomy were performed in 60 % of patients without relapses, while only 45 % of them required such surgery. Prospective study during observation has found that two patients from the first group and 12 patients from the second group had relapses of the disease. Conclusions. Therefore, the relapse risk prognostic scale concerning nodular forms of goiter is an effective method to prevent their relapses.